Adolf Ištvan – a Romani legionnaire from Bohusoudov: from research into his letters - Viková, Lada (Romano džaniben, 2018)
The case study describes the life of a Romani legionnaire, Adolf Ištvan from Bohusoudov, who by his participation in the Legions became involved in the so-called great history of the newly emerging state. During the World War II he became – like most of inhabitants from this Romani settlement – the victim of Nazi genocide. The microhistorical study focuses on the analysis of A. Ištvan’s requests from 1923–1936 sent to the Office of Legions at the Ministry of Defense of the Czech Republic. These fragments are set in a broader contemporary context, a biography of the main protagonist and, above all, of the local realities, as they could be reconstructed from archive sources. The study thus complements the existing knowledge of the Bohusoudov´s Romani settlement through a more detailed description of the life of a particular member, as well as through an analysis of archival records concerning the colony in Bohusoudov, mainly from 1919–1945. To a certain extent, the study reveals the role of the local council in maintaining or deepening the border between the Romani colony and the non-Romanipopulation. For example already at the end of 1938, the town councilors actively tried to take advantage of the changing political situation and agreed to move the Roma to "a concentration camp". The author thus presents new also findings about the changes in the relations of members of the state apparatus towards the Romani citizens.